The health‐nutrition dimension: a methodological approach to assess the nutritional sustainability of typical agro‐food products and the Mediterranean diet. (27th February 2018) - Azzini, Elena; Maiani, Giuseppe; Turrini, Aida; Intorre, Federica; Lo Feudo, Gabriella; Capone, Roberto; Bottalico, Francesco; El Bilali, Hamid; Polito, Angela
Abstract: BACKGROUND: The aim of this paper is to provide a methodological approach to evaluate the nutritional sustainability of typical agro‐food products, representing Mediterranean eating habits and included in the Mediterranean food pyramid. RESULTS: For each group of foods, suitable and easily measurable indicators were identified. Two macro‐indicators were used to assess the nutritional sustainability of each product. The first macro‐indicator, called 'business distinctiveness', takes into account the application of different regulations and standards regarding quality, safety and traceability as well as the origin of raw materials. The second macro‐indicator, called 'nutritional quality', assesses product nutritional quality taking into account the contents of key compounds including micronutrients and bioactive phytochemicals. For each indicator a 0–10 scoring system was set up, with scores from 0 (unsustainable) to 10 (very sustainable), with 5 as a sustainability benchmark value. The benchmark value is the value from which a product can be considered sustainable. A simple formula was developed to produce a sustainability index. CONCLUSION: The proposed sustainability index could be considered a useful tool to describe both the qualitative and quantitative value of micronutrients and bioactive phytochemical present in foodstuffs. This methodological approach can also be applied beyond the Mediterranean, to food products in other world regions. © 2018 Society of Chemical Industry